Pemanfaatan Ekstra Daun Kelor (Moringacae olievera) sebagai Upaya Pencegahan Stunting pada Balita di Desa Cinta Rakyat Percut Sei Tuan - Ahmad Ghifari Alamsyah; Putri Mayang Sari; Chusnul Hidayati; Poetriku Pradhana; Zaura Lestari; Ahmad Perdana Indra (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
Stunting often occurs in children aged 12-36 months. Children who experience stunting at this stage are usually difficult to achieve optimal height in the next period. Efforts to increase stunting can be done by expanding knowledge about improving eating behavior in children.Cinta Rakyat Village is the name of an area in Percut Sei Tuan District, Deli Serdang Regency which is the target of stunting prevention by UINSU 79 KKN students. Stunting prevention can be done by using Moringa leaves. The purpose of this activity is to increase knowledge to the community in the Cinta Rakyat Village area by utilizing Moringa leaf extract. The target of this activity is to increase public knowledge about stunting, and to increase community participation in local potentials to improve nutrition for children under five, such as using Moringa leaf extract as a food additive. The method of implementation is to carry out counseling by providing material on the definition of stunting, the causes of stunting for toddlers, how to prevent stunting, the benefits of Moringa leaves to prevent stunting and how to make additional food from Moringa leaf extract. The results of the evaluation of this activity show that the community can distinguish between those who are in the stunting category, which is low in height, only a genetic factor, and the community understands the benefits of Moringa leaf extract for stunting prevention. After this activity, it is hoped that the people of Cinta Rakyat Village can use the Moringa leaves (extract) in their daily lives to prevent stunting in Cinta Rakyat Village.